Exploring the Development of a Proposal for Sustainability Summer Camp - Whitaker, Angela (My University, 2015)
Challenges such as climate change and decreasing natural resources bring increased focus on the goals of sustainable development. The 21st century will need people with the specific knowledge and problem solving skills to address sustainability. Americans are reported to be misinformed when compared with citizens in other developed countries. Education is key to address this limitation and meet the demand for environmental literacy. Nonformal education has a role in the efforts needed, extending learning opportunities beyond the traditional classroom. In response to this need, the purpose of this paper is to explore the development of a proposal for a sustainability-themed summer camp to be held on the University of Wisconsin-River Falls campus. The proposed residential camp program for middle school students will use the campus as a living laboratory. University faculty and student counselors will lead participants in a structured yet fun, learner-centered curriculum. A program planning model was used to guide development of the proposal. The author?s experience working with youth camps and recent coursework in grant-writing and teaching methods were also used in the program planning process. The resulting proposal includes analysis of the planning context, program and learning objectives, learning transfer strategies, an evaluation plan, a suggested budget, a marketing plan, and an implementation timeline. The proposal is ready for presentation and discussion with department administration. Challenges and opportunities anticipated for running the proposed program are addressed. Suggestions for modifications to the proposal are given, along with benefits and drawbacks for each option. The proposed program presents opportunities for partnerships and grants, as well as longitudinal and action research projects.